2009
DOI: 10.1120/jacmp.v10i3.2834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the eclipse electron Monte Carlo dose calculation for small fields

Abstract: Varian Medical Systems (Palo Alto, CA) has implemented the Monte Carlo electron dose calculation algorithm (eMC) in the Eclipse treatment planning system. Previous algorithms for electron treatment planning were limited in their calculation ability for small field depth doses and monitor units. An old rule of thumb to approximate the limiting cutout size for an electron field was determined by the lateral scatter equilibrium and approximated by E (MeV)/2.5 in centimeters of water. In this study, we compared eM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
3
26
0
Order By: Relevance
“…While these implementations of Monte Carlo are available for clinical treatment planning, previous publications have shown that they may be inaccurate for small field dose calculations. 14,15 Further, it is well know that the Monte Carlo method is advantageous in calculating accurate dose distributions at air-tissue interfaces when compared to pencil beam algorithms, 16 and an accurate Monte Carlo model of the True-Beam will thus be beneficial to all electron therapy techniques. Moreover, the current implementation in the Eclipse TPS does not allow planning of dynamic electron radiation therapy techniques including multiple mechanical axes motions such as gantry and couch.…”
Section: Introductionmentioning
confidence: 99%
“…While these implementations of Monte Carlo are available for clinical treatment planning, previous publications have shown that they may be inaccurate for small field dose calculations. 14,15 Further, it is well know that the Monte Carlo method is advantageous in calculating accurate dose distributions at air-tissue interfaces when compared to pencil beam algorithms, 16 and an accurate Monte Carlo model of the True-Beam will thus be beneficial to all electron therapy techniques. Moreover, the current implementation in the Eclipse TPS does not allow planning of dynamic electron radiation therapy techniques including multiple mechanical axes motions such as gantry and couch.…”
Section: Introductionmentioning
confidence: 99%
“…Known limitations for eMC calculation of electron beams with energies ≤6E include 16 differences in up to 5% between measured and calculated outputs for 6E electron beams and differences in up to 14% for circular inserts with a diameter of 3 cm at an extended SSD of 115 cm. 17 Approximations of the electron path in the direction distribution and dose deposition determine whether large sphere sizes for the electron transport are used in eMC. 18 However, several studies demonstrate that eMC can predict dose distributions for high-energy electron beams with high accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The accuracy of the Eclipse eMC algorithm has been evaluated in terms of optimal calculation parameters, (4) accuracy in heterogeneous and homogeneous phantoms, (5) radiochromic film verification, (6) and small field dose calculation. (7) Currently, radiochromic film is used to perform eMC verification measurements and has been shown to agree within 2%/1 mm with measurements taken using an ionization chamber, and 2%/2 mm with an eMC algorithm. (8) However, using radiochromic film can require significant time to prepare the film for use and to read out the resulting exposure.…”
Section: Introductionmentioning
confidence: 98%